Intimal thickening in arteries of rats treated with synthetic sex hormones. - Gammal, E. B. (1976)
The effect of ethynyl oestradiol and chlormadinone acetate, separately and combined, on the aorta, carotid, mesenteric and renal arteries of female rats was studied using light and scanning electron microscopy. The hormones were injected daily for either 30 or 90 days. The most constant finding was intimal thickening which consisted mainly of areas of subendothelially located smooth muscle cells. Each artery was given a score from 0 to 3 according to the degree of development of these areas. Ethynyl oestradiol, unlike chlormadinone acetate, was associated with sustained significant enhancement of both incidence and degree of intimal thickening. With the combined treatment, the degree of intimal thickening in the 30-day group was not appreciably different from that obtained with oestrogen alone. However, in the 90-day group it was significantly less in arteries other than the aorta, suggesting that the progestogen inhibited the enhancing effect of the oestrogen on the proliferative process in these arteries.